2022
DOI: 10.1371/journal.pone.0264646
|View full text |Cite|
|
Sign up to set email alerts
|

Ameliorations in dyslipidemia and atherosclerotic plaque by the inhibition of HMG-CoA reductase and antioxidant potential of phytoconstituents of an aqueous seed extract of Acacia senegal (L.) Willd in rabbits

Abstract: The assigned work was aimed to examine the capability of phytoconstituents of an aqueous seed extract of Acacia senegal (L.) Willd to inhibit HMG-CoA reductase and regression of the atherosclerotic plaque. The chemical fingerprinting of the test extract was assessed by LC-MS/MS. Consequently, the analyses of in-vitro, in-vivo, and in-silico were executed by using the standard protocols. The in-vitro assessment of the test extract revealed 74.1% inhibition of HMG-CoA reductase. In-vivo assessments of the test e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…HMGCR is a well-known rate-limiting transmembrane enzyme, which is regulated by multiple feedback mechanisms and involved in catalyzing the conversion of HMG-CoA to mevalonate, a precursor of sterols including cholesterol synthesis. , Inhibition of cholesterol biosynthesis by blocking HMGCR in the liver results in the increased clearance of LDL from plasma by multiple methods of reverse cholesterol transport and through activation of sterol regulatory element-binding protein-2 (SREBP-2) . PCSK9, a serine protease, is another target that mediates the absorption of LDL via LDLR, which is principally accountable for eliminating plasma cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…HMGCR is a well-known rate-limiting transmembrane enzyme, which is regulated by multiple feedback mechanisms and involved in catalyzing the conversion of HMG-CoA to mevalonate, a precursor of sterols including cholesterol synthesis. , Inhibition of cholesterol biosynthesis by blocking HMGCR in the liver results in the increased clearance of LDL from plasma by multiple methods of reverse cholesterol transport and through activation of sterol regulatory element-binding protein-2 (SREBP-2) . PCSK9, a serine protease, is another target that mediates the absorption of LDL via LDLR, which is principally accountable for eliminating plasma cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…According to Fran et al [ 22 ], flavonoids (isoflavones) capture radicals before they can damage a cell, quenching active singled oxygen, and decomposing hydrogen peroxide without creating radicals. The Acacia seed extract-treated rabbits had higher levels of antioxidants such as catalase, SOD, and GSH, which are used to scavenge and destroy free radicals, while also having lower levels of free radicals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, the In Vivo studies demonstrated inhibition of HMG-CoA reductase. Apart from that they also performed an In silico study against HMG-CoA reductase and three compounds of extracts involving linoleic acid, flavan-3-ol, and eicosanoic acid which revealed a potent and strong interaction between the docked complex [15].…”
Section: Literature Reviewmentioning
confidence: 99%